Do Former Audit Firm Partners on Audit Committees Procure Greater Nonaudit Services from the Auditor? - Naiker, Vic; Sharma, Divesh S.; Sharma, Vineeta D. (The Accounting Review, 2013)
ABSTRACT: To address potential threats to auditor independence, the Sarbanes-Oxley Act of 2002 (SOX) requires the audit committee to pre-approve nonaudit services (NAS) procured from the auditor. However, the presence of a former audit firm partner (FAP) affiliated with the current auditor on the audit committee could undermine the audit committee's due diligence over the NAS pre-approval process. To alleviate such concerns, the Securities and Exchange Commission approved a three-year “cooling-off” period for appointing audit firm alumni as independent directors. Our analyses show that the presence of both affiliated and unaffiliated FAPs on audit committees does not lead to greater NAS procured from the auditor; rather, FAPs reduce NAS procured from the auditor. Moreover, NAS decline significantly following the appointment of FAPs to the audit committee. Further tests suggest the three-year cooling-off period may not be warranted and deserves further investigation. Our study raises important implications for regulators, policy makers, corporate boards, and future research. Data Availability: Data are publicly available from sources identified in the text.